2007
DOI: 10.1111/j.1556-4029.2007.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Fatal Acetaminophen Overdose Without Liver Necrosis

Abstract: Two unusual cases of suicidal overdose of acetaminophen (paracetamol) without the usual extensive centrilobular necrosis of the liver are reported. Both cases were subjected to comprehensive drug screening by immunoassay, and a combination of gas chromatography with mass spectrometry, nitrogen detection, and electron capture detection. Acetaminophen was detected in both cases. No other drugs were detected in case #1, and only a small amount of olanzapine (<0.1 mg/L) was detected in case #2. No anatomical cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Under the optimized and validated conditions, VA‐DLLME‐TLC‐image analysis method was applied for the quantitative determination of APAP in blood and tissue samples from above case. Results obtained by TLC‐image analysis were in closed agreement with the results obtained by GC–MS analysis and previous case reports [40,41]. The amount of APAP detected in blood and stomach content by TLC‐image processing and GC–MS are shown in Table 2.…”
Section: Resultssupporting
confidence: 89%
“…Under the optimized and validated conditions, VA‐DLLME‐TLC‐image analysis method was applied for the quantitative determination of APAP in blood and tissue samples from above case. Results obtained by TLC‐image analysis were in closed agreement with the results obtained by GC–MS analysis and previous case reports [40,41]. The amount of APAP detected in blood and stomach content by TLC‐image processing and GC–MS are shown in Table 2.…”
Section: Resultssupporting
confidence: 89%
“…The blood paracetamol concentration (221mg/L) was high and indicated that an excess of the analgesic had been taken and was sufficiently elevated, to have potentially induced liver necrosis if the drug had been ingested several days earlier. However, the concentration was well below that potentially associated with the exceptionally rare instances of fatal acute toxicity [1][2][3] .…”
Section: Case Reportmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] Various other analytical methods have also been applied to detect APAP and its metabolites, such as high performance liquid chromatography (HPLC) in combination with accelerator mass spectrometry (AMS), [26] diode-array detection (DAD), [8] chemical reaction interface for mass spectrometry (CRIMS), [27] UV, [9] as well as capillary electrophoresis (CE) with UV detection. [19][20][21][22][23][24][25] Various other analytical methods have also been applied to detect APAP and its metabolites, such as high performance liquid chromatography (HPLC) in combination with accelerator mass spectrometry (AMS), [26] diode-array detection (DAD), [8] chemical reaction interface for mass spectrometry (CRIMS), [27] UV, [9] as well as capillary electrophoresis (CE) with UV detection.…”
Section: Introductionmentioning
confidence: 99%
“…Usually APAP is quantified by immunoassay techniques, either as part of a general screen or as specific target. [19][20][21][22][23][24][25] Various other analytical methods have also been applied to detect APAP and its metabolites, such as high performance liquid chromatography (HPLC) in combination with accelerator mass spectrometry (AMS), [26] diode-array detection (DAD), [8] chemical reaction interface for mass spectrometry (CRIMS), [27] UV, [9] as well as capillary electrophoresis (CE) with UV detection. [28] In particular, hyphenated HPLC-mass spectrometry (LC-MS) has shown great potential, because of its specificity and its ability to identify structurally-related substances that could bias the result of immunoassay analysis.…”
Section: Introductionmentioning
confidence: 99%